2018
DOI: 10.1007/s00109-018-1664-3
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine protects against myocardial ischemia/reperfusion injury by inhibiting excessive autophagy

Abstract: TMZ improved cardiac function, alleviated myocardial injury and oxidative stress, and reduced the myocardial infarct area and apoptosis. TMZ inhibited MI/R-induced myocardial autophagy, H/R-induced H9c2 cell apoptosis, and autophagy flux. The effect of TMZ on autophagy was repressed by LY294002. TMZ protected against MI/R injury by inhibiting excessive autophagy via activating the AKT/mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 49 publications
7
56
0
1
Order By: Relevance
“…Ischemia-reperfusion injury (IRI) is serious tissue damage arising from the restoration of the blood supply after ischemia. 1 The lack of oxygen, adenosine triphosphate, and nutrients from the blood leads to functional and metabolic disorders of the organs. As a consequence, restoration of the blood flow results in the oxidative damage and inflammation rather than recovery.…”
mentioning
confidence: 99%
“…Ischemia-reperfusion injury (IRI) is serious tissue damage arising from the restoration of the blood supply after ischemia. 1 The lack of oxygen, adenosine triphosphate, and nutrients from the blood leads to functional and metabolic disorders of the organs. As a consequence, restoration of the blood flow results in the oxidative damage and inflammation rather than recovery.…”
mentioning
confidence: 99%
“…28 However, under pathological conditions, impaired or over-activated autophagy promotes cell injuries by accumulating intracellular damaged components, inducing excessive oxidative stress and promoting apoptosis death. 29 In present study, there was a close relationship between LC3-II/I ratio and endothelial injury, indicating that autophagy was involved in bubble-induced endothelial dysfunction. The results of pre-treatment with autophagy inhibitor 3-MA showed that it inhibited the increase of LC3-II/I ratio and significantly alleviated endothelial injury caused by microbubble contacts for 10, 20 and 30 minutes, confirming that autophagy promoted endothelial injury under these microbubble contact periods.…”
Section: Discussionsupporting
confidence: 61%
“…As a basal cellular process response to many stressors, autophagy may represent a cell protection mechanism to guarantee an efficient cytosolic clearance and maintain bioenergetics homoeostasis . However, under pathological conditions, impaired or over‐activated autophagy promotes cell injuries by accumulating intracellular damaged components, inducing excessive oxidative stress and promoting apoptosis death . In present study, there was a close relationship between LC3‐II/I ratio and endothelial injury, indicating that autophagy was involved in bubble‐induced endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 49%
“…Patients who met any of the following criteria were excluded from this trial: (1) acute myocardial infarction, cardiogenic shock, lethal cardiac arrhythmias, cardiac tamponade, pulmonary embolism, acute myocardial infarction, and other severe conditions; (2) serious primary diseases of lung, liver, kidney, endocrine system, or hematological system; (3) pregnancy or lactation; (4) allergic constitution or allergy to multiple drugs; (5) patients with mental illness, mental disorders, dementia or malignant tumor; (6) participants who have taken Chinese medicine (including proprietary Chinese medicines) or participated in other clinical trials in the past 2 weeks; and (7) patients who had incomplete clinical data.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Previous studies have found that Chinese herbal medicine with qi-invigorating effect can signi cantly improve the myocardial energy substances ATP and PCr in rats with heart failure [5]. TMZ, which are known to regulate myocardial energy metabolism, are commonly used in the treatment of heart failure to optimize energy metabolism substrates and promote glucose metabolism [6].…”
Section: Introductionmentioning
confidence: 99%